2001
DOI: 10.1007/s002210100735
|View full text |Cite
|
Sign up to set email alerts
|

Idiothetic navigation in humans: estimation of path length

Abstract: When vision is excluded humans are still able to walk back to a starting point or to a previously seen target. This performance may be mediated by path integration, based on information about movement with respect to the ground or to inertial space, that is, on substratal or inertial idiothetic cues. We intend to unravel whether, and how accurately, these two inputs act and interact on the translatory component of this navigation performance. Subjects were asked 1) to reproduce a path they had walked, and 2) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
206
2
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(222 citation statements)
references
References 28 publications
13
206
2
1
Order By: Relevance
“…This could either involve navigating to a location that participants have previously seen before being blindfolded (Elliott, 1987;Philbeck et al, 1997), or returning to the starting position of a single-element (Mittelstaedt and Mittelstaedt, 2001) or multielement (Loomis et al, 1993) path. Across such studies, participants are very systematic in the errors that they make, demonstrating the existence of clear nonrandom principles underlying performance.…”
Section: Development Of Path Integrationmentioning
confidence: 99%
“…This could either involve navigating to a location that participants have previously seen before being blindfolded (Elliott, 1987;Philbeck et al, 1997), or returning to the starting position of a single-element (Mittelstaedt and Mittelstaedt, 2001) or multielement (Loomis et al, 1993) path. Across such studies, participants are very systematic in the errors that they make, demonstrating the existence of clear nonrandom principles underlying performance.…”
Section: Development Of Path Integrationmentioning
confidence: 99%
“…For legged locomotion, idiothetic (nonvisual) information about movement is available with respect to the surface of support and with respect to inertial space (the general background of resistance to acceleration) (Mittelstaedt and Mittelstaedt 2001). In Gibson's (1966) classification of perceptual systems, the substrate variant of idiothetic information is detected by the haptic perceptual system and the inertial variant is detected by the basic orienting system (statocyst, vestibular organ).…”
Section: Introductionmentioning
confidence: 99%
“…In Gibson's (1966) classification of perceptual systems, the substrate variant of idiothetic information is detected by the haptic perceptual system and the inertial variant is detected by the basic orienting system (statocyst, vestibular organ). The substrate variant seems to be the more general basis for a non-visual ability to measure traveled distance (Etienne et al 1998), an ability common to humans (Isenhower et al 2012;Klatzky et al 1990;Mittelstaedt and Mittelstaedt 2001;Schwartz 1999;Turvey et al 2009), dogs (Séguinot et al 1998), fiddler crabs (Walls and Layne 2009), spiders (Barth 2004;Seyfarth and Barth 1972), and desert ants (Wittlinger et al 2006(Wittlinger et al , 2007Wohlgemuth et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Humans are also quite competent at navigating to a target without visual input. Non-visual inputs are internally generated as a result of one's body movements (Chance, Gaunet, Beall, & Loomis, 1998;Mittelstaedt & Mittelstaedt, 2001). This source of information, often referred to as 'idiothetic information' is provided by muscles and joints, motor efferent signals and vestibular information generated as a result of changes in linear or rotational movement velocities (Tversky, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have shown, similar to Thomson, that blindfolded humans are able to navigate relatively successfully towards a target, his suggestion of a time limiting component has not been replicated (Fukusima, Loomis, & Da Silva, 1997;Rieser, Ashmead, Talor, & Youngquist, 1990), with many authors finding that participants become less accurate in their estimation if the distance is increased (Corlett, Patla, & Williams, 1985;Fukusima et al, 1997;Glasauer, Amorim, Vitte, & Berthoz, 1994;Loomis, Da Silva, Fujita, & Fukusima, 1992;Mittelstaedt & Mittelstaedt, 2001;Rieser et al, 1990;Steenhuis & Goodale, 1988). Indeed, there is good evidence to suggest that other factors apart from time can contribute to successful non-visual distance estimation.…”
Section: Introductionmentioning
confidence: 99%